Pengaruh Sistem Informasi Digital Berbasis Website dalam Meningkatkan Pelayanan Publik di BLU UPBU Kelas 1 Kalimarau - Fadillah, Faizal Amirudin; Soebagio, Agoes; Sonhaji, Imam (Jurnal Ground Handling, 2025)
in today's digital era, the role of information technology is crucial in supporting performance and public services, including in the air transportation sector. An airport’s official website serves as a strategic medium for providing accurate, fast, and easily accessible information for service users, particularly passengers. As a primary gateway for public mobility, airports are required to present relevant and up-to-date information.This research aims to: (i) identify the website features used to provide passenger information services at Kalimarau Airport, and (ii) determine what additional features could be incorporated to further develop passenger information services at Kalimarau Airport.This study employs a qualitative descriptive analysis technique, presenting the results systematically to provide a clear overview. Interviews were also conducted with the public relations staff of Kalimarau Airport. The data for this research were collected through observation, interviews, and documentation. The object of this study is the Kalimarau Airport website.The results show that the features currently available on the Kalimarau Airport website do not yet fully meet the information needs expected by passengers. Further development is needed, including the addition of key features such as a lost and found information service, as well as the provision of scannable barcodes to facilitate quick access to various necessary information for users.The conclusion of this research is that the development and addition of features on the Kalimarau Airport website are essential to improving the quality of information services for passengers. Ultimately, this is expected to enhance the overall passenger experience and comfort while at the airport.